Social Capital and the Political Economy of Recovery from Injury - Butler, Dr. Mary (International Journal of Innovative Research in Medical Science, 2017)
Injury has long been recognized as a contributor to disability, but there is little data on how processes related to social capital, may influence the emergence of disability. This article aims to present findings from the qualitative arm of a multi-method Prospective Outcomes of Injury Study (POIS), which was established to examine factors influencing recovery following injury in New Zealand. A maximum diversity sample of nineteen injured people, aged 18-64, was chosen from 2856 participants in the quantitative POIS study (Butler, Derrett & Colhoun, 2009). Participants in the study were all on the New Zealand Accident Compensation Corporation's (ACC's) injury entitlement register. Interviews were carried out at six and twelve months after injury, which offered a unique insight into the unfolding impact of the injury on social networks. The findings describe a political economy of social capital that reflects the inverse care law (Hart, 1971). This can be summarised by the observation that those with higher levels of social capital were able to ask for care in ways that maintained the invisibility of the labour involved and also contributed to the growth of social capital. Those with lesser degrees of social capital used strategies to make their needs less visible in order not to lose face and this contributed to the erosion of social capital. The findings indicate the utility of Bourdieu's (1986) conceptualisation of social capital to elucidate the dynamics implicit in the practice of giving and receiving resources following an injury.